Amyloid-beta peptide A beta p3-42 affects early aggregation of full-length A beta 1-42 - Sanders, Hiromi M.; Lust, Robert M.; Teller, Jan K. (East Carolina University, 2009)
The major amyloid beta (Aβ) peptides found in the brain of familial and late onset Alzheimer’s disease include the full-length Aβ1-42 and N-terminally truncated, pyroglutamylated peptides Aβp3-42 and Aβp11-42. The biophysical properties of Aβ1-42 have been extensively studied, yet little is known about the other modified peptides. We investigated the aggregation kinetics of brainspecific Aβ peptides to better understand their potential roles in plaque formation. Synthetic peptides were analyzed individually and in mixtures representing various ratios found in the brain. Spectrofluorometric analyses using Thioflavin-T showed that the aggregation of Aβ1-42 was faster compared to Aβp3-42; however, Aβp11-42 displayed similar kinetics. Surprisingly, mixtures of fulllength Aβ1-42 and Aβp3-42 showed an initial delay in beta-sheet formation from both equimolar and non-equimolar samples. Electron microscopy of peptides individually and in mixtures further supported fluorescence data. These results indicate that Aβ-Aβ peptide interactions involving different forms may play a critical role in senile plaque formation and maintenance of the soluble Aβ pool in the brain. Originally published Peptides, Vol. 30, No. 5, May 2009
Keywords: Alzheimer's disease; Amyloid beta peptides; Aggregation; Pyroglutamate